Ultrafast Responsive Non‐Volatile Flash Photomemory via Spatially Addressable Perovskite/Block Copolymer Composite Film. (6th April 2020) - Chang, Yu‐Hsiang; Ku, Chia‐Wei; Zhang, Yi‐Hua; Wang, Hsiang‐Chen; Chen, Jung‐Yao
Abstract: The exotic photophysical properties of organic–inorganic hybrid perovskite with long exciton lifetimes and small binding energy have appeared as promising front‐runners for next‐generation non‐volatile flash photomemory. However, the long photo‐programming time of photomemory limits its application on light‐fidelity (Li‐Fi), which requires high storage capacity and short programming times. Herein, the spatially addressable perovskite in polystyrene‐ block ‐poly(ethylene oxide) (PS‐ b ‐PEO)/perovskite composite film as an photoactive floating gate is demonstrated to elucidate the effect of morphology on the photo‐responsive characteristics of photomemory. The chelation between lead ion and PEO segment promotes the anti‐solvent functionalities of the perovskite/PS‐ b ‐PEO composite film, thus allowing the solution‐processable poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) to act as the active channel. Through manipulating the interfacial area between perovskite and P3HT, fast photo‐induced charge transfer rate of 0.056 ns −1, high charge transfer efficiency of 89%, ON/OFF current ratio of 10 4, and extremely low programming time of 5 ms can be achieved. This solution‐processable and fast photo‐programmable non‐volatile flash photomemory can trigger the practical application on Li‐Fi. Abstract : The spatially addressable perovskite in a polystyrene‐ block ‐poly(ethylene oxide) (PS‐ b ‐PEO)/perovskite composite film as an photoactive floating gate is demonstrated. By manipulating the interfacial area between the perovskite and active channel, a fast photo‐induced charge transfer rate of 0.056 ns −1, high charge transfer efficiency of 89%, ON/OFF current ratio of 10 4, and extremely low programming time of 5 ms can be achieved.